Preserving security using crisscross AES and FCFS scheduling in cloud computing. (2019) - Ramkumar, K.; Gunasekaran, G.
Cloud computing is a developing technology in distributed computing which provides pay service model as per user need and requirement. Cloud includes the collection of virtual machine which have both computational and storage facility. The objective of cloud computing is to provide effective process to hyper distributed resources. Nowadays, cloud system is developing and faces many challenges, two of them are scheduling process and other main challenge is security. Scheduling states about how scheduler adapts its scheduling strategy, according to the changing set of morals to control the order of work to be implemented by a computer system. In this research paper, a scheduling algorithm of collocate first come first server (FCFS) of supremacy elements is proposed where the system efficiency is improved using FCFS in parallel manner. FCFS is simple and fast. To address security problem, crisscross advance encryption standard (AES) is proposed by increasing the security in the cloud through the grid manner. AES uses an identical key for both encrypting and decrypting the text. Aggregate of this proposed work is to enhance the system efficiency and security by using the both crisscross AES and collocate FCFS of supremacy elements.